George Reavey (1907-1976) : The endless chain, a literary biography - O'Connell, Sandra Andrea (Trinity College (Dublin, Ireland). School of English, 2006)
George Reavey (1907-1976) was an experimental poet, an enterprising publisher and literary agent and an esteemed critic and translator of Russian literature. His literary beginnings can be traced back to Cambridge, where he was a central part of group that looked beyond the tranquil college greens for new influences and inspirations. The group embraced international Modernism, which found expression in the magazine Experiment which they edited. For the next decade, following his graduation in English (BA Hons.) from Cambridge in 1929, Reavey became closely linked with the Modern movement. In Paris, in the early thirties, he started a literary agency, placing French authors with English publishers and gaining opportunities for English-language writers abroad. His greatest achievement was to secure the publication of Samuel Beckett’s novel Murphy by Routledge, a work perceived as difficult and turned down by over forty publishers. In the mid 1930s, he emerged within a group of writers and painters that brought the controversial artistic force of Surrealism to London.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin